An Electrochemical Sandwich Immunosensor Based on Signal Amplification Technique for the Determination of Alpha-Fetoprotein - Shen, Changming; Wang, Lin; Zhang, Hongyan; Liu, Shaojuan; Jiang, Jianwei (Frontiers in Chemistry, 2020)
The synthesis of Au nanocubes is used to label alpha-fetoprotein antibody (anti-AFP) and horseradish peroxidase (HRP) to form an immune complex for antibody detection. Graphene oxide-methylene blue-gold nanoparticles (GO-MB-AuNPs) nanocomposites were used as the immunosensing platform. This proposed sandwich-type immunoassay shows good performance. This method establishes a feasible amperometric immunoassay method for sensitive analysis of AFP in serum samples. Under the optimal experimental conditions, the DPV current response of the immunosensor is proportional to the logarithmic value of the AFP concentration. The linear detection range can achieve to 0. 005-20 ng/mL with a detection limit of 1.5 pg/mL. The proposed immunosensor has good precision, selectivity and stability, and can be used for AFP determination in clinical tests.